Rights of Children from Interfaith Marriages: Child Registration Case in Semarang, Indonesia - Ruth Elita; Fathiyyah Layla; Chelsy Naristya; Zulfhan Akbar; Miftahul Jannah (Contemporary Issues on Interfaith Law and Society, 2024)
This paper investigates the rights of children born into interfaith marriages, focusing on child registration in Semarang. In a multicultural society like Indonesia, children from interfaith unions face complex legal and social challenges. This study explores the nuances of child registration in Semarang, addressing the legal framework, social dynamics, and implications for children's rights. Beginning with an overview of Indonesia's legal context, the paper emphasizes the importance of civil registration in establishing a child's legal identity and access to rights and services. It examines the hurdles encountered by interfaith families in navigating registration procedures, including issues of parental consent, religious affiliation, and administrative barriers. The study also delves into the social aspects of child registration in Semarang, analyzing how cultural norms, religious beliefs, and community attitudes shape the registration process and affect children's legal recognition. Challenges such as social stigma, discrimination, and bureaucratic inefficiencies are highlighted as obstacles to obtaining birth certificates and official documentation for children from interfaith backgrounds. Furthermore, the paper discusses the implications of insufficient child registration for children's rights, emphasizing the importance of equal treatment and legal recognition for all children, regardless of their parents' religious affiliations or cultural backgrounds. By examining the child registration case in Semarang, Indonesia, this study contributes to broader discussions on the rights of children from interfaith marriages and advocates for inclusive policies and practices. Addressing legal and social barriers to registration and promoting interfaith dialogue can ensure that every child enjoys their fundamental rights and opportunities for a fulfilling future.